2016
DOI: 10.1515/jcbtp-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Financial Education of Children and Youth

Abstract: More and more individuals are becoming overindebted and facing difficulties in managing personal finance. On the other hand, financial products are becoming more and more complex, with numerous concealed risks. The level of financial literacy of youth and children is unsatisfactory both in the region and globally. Such a situation could lead to personal problems (financial distress), aggravated financial stability, with reverse adverse implications on economic growth. Many international studies have also confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 1 publication
0
19
0
10
Order By: Relevance
“…In their text Fabris and Luburić (2016) mention that the opening point of the strategy should be to answer the questions: "Where are we now?" and "Where do we want to be in the future?".…”
Section: Research Of the Financial Literacy Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…In their text Fabris and Luburić (2016) mention that the opening point of the strategy should be to answer the questions: "Where are we now?" and "Where do we want to be in the future?".…”
Section: Research Of the Financial Literacy Levelmentioning
confidence: 99%
“…The involvement of other participants is also important in order to increase credibility, increase the number of experts and the amount of resources available. At an imaginary peak, although the authors of the text in the ideal case see the Central bank however in the Czech Republic the position is held by the Ministry of Finance (Fabris, Luburić, 2016).…”
Section: Procedures For the Introduction Of The Financial Education Inmentioning
confidence: 99%
“…A large number of studies have confirmed the link between education and poverty, through which the importance of the financial education for youth and children is highlighted. 4 Looking closer, it will be seen that the national priorities of the developed countries are, at the same time, some of the key indicators of the quality of life.…”
Section: Money and The Indicators Of Quality Of Lifementioning
confidence: 99%
“…These new characteristics became a distinguishing factor in banking competition, and are described as "financial engineering" by Quelhas (1996). Fabris & Luburić (2016) presented the growing of complexity of financial products that justify the need to increase financial literacy in youth generation.…”
Section: Introductionmentioning
confidence: 99%